Efeitos de cádmio e chumbo no desenvolvimento de rúcula (Eruca sativa L.), rabanete (Raphanus sativus L.) e feijoeiro (Phaseolus vulgaris L.) em solução nutritiva - Cannata, Marcele Gabriel (2011)
The goal of this work was to investigate the effect of five increasing contents of Cd (0, 0.025, 0.1, 0.5 and 1 mg L-1) and Pb (0, 0.25, 1, 5 and 10 mg L-1), in radish, arugula and bean plants cultivated in greenhouse at the Department of Soil Science and analyzed in the laboratories of the Department of Chemistry of the Federal University of Lavras - MG. This research, which is a compilation of five scientific papers, was based on the study of the following parameters: contents of Cd and Pb in radish, arugula and bean plants, as well as their relationship with the plant´s development; contents, accumulation and translocation of Cd and Pb in bean plants cultivated under nutritive solution and two latosols. Cd and Pb translocate poorly in radish, arugula and bean plants; the deleterious effect is due to deposition of stable chelates in roots, particularly of Pb; 1 mg L-1 Cd and 10 mg L-1 Pb were the maximum tolerable contents for arugula; radish and arugula submitted to 0.025 mg L-1 Cd developed more than in the control treatment because of better absorption of Zn; Pb and Cd reduced the production of dry matter of roots and shoots; increment in the production of fruits (husks and grains) in bean plants under low contents of Cd (0.025 and 0.1 mg L-1) and Pb (0.25 and 5 mg L-1) is due to larger absorption of Zn (similar effect was observed in latosols); in general, Cd and Pb caused decreasing in contents, accumulation and translocation of macro and micronutrients in bean plants; the low translocation of Cd and Pb with increasing production of fruits either in nutritive solution or soils does not suggest the consumption of grains.